Pengaruh Financial Distress dan Audit Delay Pada Voluntary Auditor Switching dengan Opini Audit Sebagai Variabel Pemoderasi - Darma Yanti, Ni Putu Mega; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2018)
The aim of this study was to determine the effect of financial distress and audit delay on voluntary auditor switching with audit opinion as a moderating variable. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in year 2012-2016 with a population of 148 companies. Determination of the sample used was purposive sampling technique with as many as 28 companies that meet the criteria. The technique of analysis used in this research was descriptive statistical analysis, logistic regression analysis and Moderation Regression Analysis (MRA). The result of the test in this study showed that audit delay has positive effect on voluntary auditor switching and financial distress has no effect on voluntary auditor switching. Audit opinion was not able to moderate the influence of financial distress and audit delay on voluntary auditor switching. Keywords : audit opinion, financial distress, audit delay, voluntary auditor switching